Financial Distress Prediction Using Springate and Altman Model: Based on Financial Indicators of Industrial Companies - Paramitha, Diky (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2025)
Research Aim: To develop the Altman and Springate models to estimate the likelihood of financial distress in the industrial sector for the 2015-2021. Method: Analysis of data from 52 industrial companies listed on the Indonesia Stock Exchange (2015-2021) using Altman discriminant analysis and Springate S-Score to identify financial distress. Research Finding: Out of 52 companies, 27 experienced financial distress. The Altman model demonstrated better prediction accuracy. Theoretical Contribution: This paper strengthens the validity of the Altman and Springate models in predicting financial distress in the industrial sector. Practical Implication: Provides insights for investors and management to anticipate bankruptcy risks and improve financial stability. Research Limitation: Limited to the industrial sector in Indonesia for the 2015-2021 period and relies solely on financial statement data without considering external factors.